Chronic low dose organic arsenic exposure histological changes in rats animal model colonic mucosa - Khodijah Zulkiflee (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
Arsenic is a well-documented carcinogenic agent and causes acute toxicity in many organs. Humans are exposed to arsenic in several ways such as contamination of organic arsenic-based pesticide in our water supply which presumably can affect our gastrointestinal system. Colon cancer is the second most common cancer in Malaysia that causes high morbidity and mortality. However, only few studies have been done to link chronic arsenic exposure to the development of colon carcinoma. This study aimed to investigate the effect of chronic low dose of organic arsenic exposure to colonic mucosa. Sixty Sprague Dawley rats were divided equally into control and treated groups. Treated group received oral gavage of 42.13 mg/kg of Monosodium Methanearsonate (MSMA) which equals to 1/30 of LD50 MSMA in rat, to mimic the concentration of organic arsenic in our drinking water. While control group received distilled water. Each group was further divided into 3 subgroups according to the duration of exposure either 2 months, 4 months or 6 months before they were euthanized for tissue harvesting. The specimens were processed for methylene blue staining of the luminal surface of the mucosa, hematoxylin and eosin staining for quantitative study, immunohistochemistry for p21 marker expression and scanning electron microscopic study for surface topography. Scanning electron microscopic study of the luminal surface in treated rats showed varying degrees of inflammatory reactions proportional to the duration of exposures. Colonic sample from 2-month treated group revealed colonic mucosal surface had less homogeneity in size and shape of individual glandular units with slit-like crypt orifice. However, it was still covered with a dense coat of microvilli. Colonic sample from 4-month treated group showed the individual glandular units had less distinct border and stellate- shaped of orifice and decreased in the number of microvilli. Colonic sample from 6-month treated group showed the most obvious findings where there was formation of prominent cleft that gave cerebriform appearance on colonic mucosal surface and the number of microvilli also was reduced. However, there was no obvious epithelial changes observed in full thickness H&E stained colonic mucosa of treated and control rats. The expression of p21 marker was also negative in treated and control samples. The means mitotic count per area micron square were significantly lower in 4 months and 6 months treated groups as compared to similar interval control groups respectively. In 4-month Control (M = 1106.81, SD = 296.74) and Treatment (M = 668.83, SD = 367.39) groups; t(14) = -2.625, p = 0.020. In 6-month Control (M = 974.18, SD = 686.42) and Treatment (M = 233.56, SD = 157.94) groups; t(9) = -2.341, p = 0.044. However, the difference of the mean mitotic count per micron square between control and treated groups after 2 months exposure was not significant (p > 0.05). In conclusion, chronic exposure to organic arsenic demonstrated temporal topographical changes to luminal surface of colonic mucosa and paradoxically reduction in intestinal epithelium proliferative rate.